2008
DOI: 10.1111/j.1523-5378.2008.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Four Modes of Adhesion are Used During Helicobacter pylori Binding to Human Mucins in the Oral and Gastric Niches

Abstract: Background: Helicobacter pylori causes peptic ulcer disease and gastric cancer, and the oral cavity is likely to serve as a reservoir for this pathogen. We investigated the binding of H. pylori to the mucins covering the mucosal surfaces in the niches along the oral to gastric infection route and during gastric disease and modeled the outcome of these interactions. Materials and Methods: A panel of seven H. pylori strains with defined binding properties was used to identify binding to human mucins from saliva,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 36 publications
5
101
1
1
Order By: Relevance
“…Upon infection, H. pylori primarily resides within the mucus layer, adhering to mucins, high molecular weight glycoproteins and major components of the protective layer across the upper mucous surfaces (Peek and Blaser, 2002;Lindén et al, 2008). Some works have documented the role of MUC1 in the H. pylori infection and gastric cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Upon infection, H. pylori primarily resides within the mucus layer, adhering to mucins, high molecular weight glycoproteins and major components of the protective layer across the upper mucous surfaces (Peek and Blaser, 2002;Lindén et al, 2008). Some works have documented the role of MUC1 in the H. pylori infection and gastric cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…pylori colonization of the stomach is initiated through pathogen binding to cell surface receptors expressing the sialyl-Lewis a (sLea), Lewis b (Leb), and sialyl-Lewis x (sLex) glycoconjugates (Lindén et al, 2008). The corresponding H. pylori adhesions, blood group antigen binding adhesion (BabA) and sialic acid binding adhesion (SabA), interact with these host receptors (Lindén et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Normal gastric mucosa shows cell type specific expression of secreted mucin MUC5AC in the surface epithelium (Wang et al, 2006;Lindén et al, 2010). Several studies have strongly suggested that MUC5AC forms the major receptor for H. pylori in the human stomach (Van de Bovenkamp et al, 2003;Lindén et al, 2008), and the infection of H. pylori can alter the expression of MUC5AC (Kocer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion to the gastric mucosa is important in the life cycle of H. pylori (4). As MUC5AC is an important receptor for gastric mucosa adhesion (5-7), efficient colonization of the stomach requires high expression of MUC5AC by gastric epithelial cells (8,9). Previous studies have demonstrated that the stomach epithelium reacts to H. pylori infection by activating pro-inflammatory signaling pathways (10), thereby activating innate defense mechanisms against H. pylori, which may include the downregulation of MUC5AC expression in the human gastric mucosa (2,6,11,12).…”
Section: Introductionmentioning
confidence: 99%